MODULE DESIGN DOT MATRIX LCD 16x2 DISPLAY TEXT FOR WALKING CHARACTHER MICROCONTROLER AT89C51 - Erwin Kurniawan; Drs. Soebijantoro, MMEng Drs. Soebijantoro, MMEng (Jurnal Sistem Komputer, 2003)
World of advertising is very necessary in every large and small companies, with theexistence of any advertising that is placed where it will be increasingly well knowncompany. But the ads need to be made very attractive to the recipient information in alanguage that is easy to remember by using the electronic ads to appear moreattractive with the current character format varied.In this tool is used as a viewer character LCD (writing) runs. The key pad functionsas a giver of the input signal to determine the current paper format. Obviously to beable to run the text-based microcontroller, the need for programs that can control it.